Addressing challenges of developing countries in implementing five priorities for sustainable development goals. Issue 7 (29th September 2015) - Sarvajayakesavalu, Suriyanarayanan
Abstract : As the Millennium Development Goals (MDGs) deadline approaches, UN member states have established a new, universal set of goals, i.e., Sustainable Development Goals (SDGs), to develop a global vision for sustainable development, balancing economic growth, social development, and environmental protection over the next fifteen years. There is a need to give specific attention, dependent on the capacities of nations and other national circumstances, to the different goals and targets. Focused guidelines and priorities are essential requirements for the achievement of the SDGs. The five priorities for the SDGs proposed byLu et al. (2015) are of great significance to the participating communities, as they present the right directions for the proper functioning of the Sustainable Development Goals. There will be significant challenges for developing countries to put the five priorities into practice, depending on their policies and other national settings. This article addresses the major challenges that may be faced by developing nations when implementing the SDGs.